Scholarly feminist versus internet commentator on women issues in Islam - Nurdin, Ahmad Ali (State Institute of Islamic Studies (STAIN) Salatiga, 2011)
This article discusses two different types of contemporary writings bothâscholarly feministsâ and âinternet commentatorsâ on women in Islam;particularly issues related to gender equality such as womenâs rights, statusand creation. By comparing two different groups of writers, the objective of thispaper is to discover whether there are significant differences between them onissues of women in Islam, which shed light on modern Islamic thinking. From abrief investigation of several books as representatives of scholarly feminists, andseveral websites, which publish many articles on women in Islam, asrepresentatives of Internet commentators, it is clear that both groups seem tohave similar attitude on the topic. They tried to clarify a common misperceptionof women in Islam which is commonly portrayed to be âa second classâ. Moreover,it is clear that the message of âInternet commentatorsâ seem to be moreeffective and more likely to prevail.Artikel ini membahas dua tipe tulisan-tulisan kontemporer, baik dari kalanganâfeminis terpelajarâ maupun âkomentator internetâ mengenai perempuan dalam Islam; utamanya berkaitan dengan persoalan-persoalan keadilan gender, sepertihak-hak kaum perempuan, status dan penciptaan mereka. Denganmembandingkan dua kelompok penulis ini, tujuan artikel ini adalah untukmenemukan apakah ada perbedaan signifikan antara kedua kelompok ini mengenaimasalah-masalah perempuan dalam Islam yang mewarnai pemikiran Islammodern. Dari penelitian singkat atas beberapa karya yang mewakili kaum feministerpelajar dan beberapa websites yang memublikasikan banyak artikel tentangperempuan dalam Islam, sebagai representasi dari komentator internet, jelasbahwa dua kelompok ini memiliki keserupaan sikap atas topik tersebut. Merekamencoba menjelaskan kesalahpahaman umum tentang perempuan dalam Islamyang biasanya digambarkan sebagai âkelas keduaâ. Juga tampak bahwa pesandari para komentator internet lebih efektif dan berhasil.